ANALISIS PENDEKATAN PENGAMBILAN KEPUTUSAN INVESTASI PASAR MODAL DI BEI MENGGUNAKAN PERHITUNGAN PRICE EARNING RATIO (PER) - Aulia, Nila; Putri, Tiara Amelia; Budiwitjaksono, Gideon Setyo (Jurnal Manajemen, Akuntansi, Ekonomi, 2023)
This research is to find out the decision making of investors in investing in the Capital Market by using the Price Earning Ratio (PER) calculation approach. This study uses a descriptive research method with a quantitative approach. The analysis technique uses data from data collection, data processing, and the results of data analysis as input. In this study using fundamental analysis methodology using the Price Earning Ratio (PER) to determine the condition of the stock market. The research results show that from the results of estimating intrinsic value using the price-earnings ratio method, it is determined that PT X Tbk is an undervalued company, with an intrinsic value that is higher than the market price or depressed shares. The results of estimating intrinsic value using the price-earnings ratio method show that the companies PT Y Tbk and PT Z Tbk are overvalued because their intrinsic value is lower than the market price or share value.